Comparison of Actual and Reported Macronutrient Intake in a Well-controlled Human Feeding Study (P08-003-19). (24th October 2019) - Casey, James; Reger, Heidi Iglay; LaBarre, Jennifer; Ball, Sarah; Han-Markey, Theresa; Burant, Charles; Peterson, Karen
Abstract: Objectives: Dietary guidelines are largely based on epidemiological studies that rely on memory-based dietary assessments (MBDAs) such as 24-hour recalls (24 hr). Few reports have compared actual and reported dietary intake in well-controlled feeding studies (WCFS). This study sought to directly compare discrepancies between actual dietary intake from experimental diets and reported 24 hr intake in free-living participants. Methods: Food was provided to 24 subjects (50% female, ages 24.4(3.4); BMI 23.1(2.9)) for 24 days; all diets were eucaloric. Participants were provided a standard diet (15% protein (PRO): 35% fat: 50% carbohydrate (CHO)) for 3 days and then randomly assigned to either a 21-day high fat (60% fat, HF) or a high CHO (75% CHO, HC) diet while PRO was held constant. Diets were 'typical' foods with macronutrient compositions adjusted to achieve targeted percentages, either overtly (added sugary drinks) or covertly (added coconut oil). Calories were added to maintain weight (±1 kg). Dietitians administered 4 24-hour recalls (24 hr); one after the standard diet, and once a week during the experimental diets. Actual and reported energy intake (EI) and macronutrient intakes were compared within group via Student's T-tests (α = 0.05). Results: No difference was observed between actual EI and reported EI during the standard or experimental phase for HF or HC groups. %difference was calculated as (g reported/g actual) * 100. PRO intake was over-reported by all subjects during the standard phase – 127.4% (11.3) and during the HC – 115.6% (7.2) and HF – 116.1% (5.6). PRO difference was due to over-reporting of animal PRO. During the experimental diet, HC subjects over-reported CHO – 166.4% (11.4) and under-reported fat –93.7% (4.7) while HF subjects under-reported CHO – 89.2% (6.5) and over-reported fat –119.8 (6.7). ( P < 0.05). Conclusions: In this WCFS in free-living participants, EI is accurately reported. However, subjects over-report animal PRO intake potentially due to their misreporting portion sizes of meat. When given extreme diets, subjects tended to under report the experimental macronutrient (HF or HC). This could potentially be due to covert target macronutrients in the diet. This makes use of the 24hr suspect in WCFS when macronutrients are hidden from participants. Funding Sources: This study was internally funded through researchers discretionary funds. Supporting Tables, Images and/or Graphs